The Effect of Collaborative Learning Using WordUp Application on Vocabulary Mastery - Melati, Melati; Sabarun, Sabarun; Nurliana, Nurliana (Journal of English Language and Education, 2024)
This research investigated the effect of collaborative learning with WordUp application on seventh-grade students' vocabulary mastery proficiency at MTs Raudhatul Jannah, Palangkaraya. Using Quasi-experimental design with a purposive sampling of 58 students divided into experimental and control groups, quantitative methods were employed. WordUp was utilized for collaborative learning in experimental class, whereas the control classes did not receive such intervention. The averages pretest scores of the experimental class was 66.21, compared to 57.12 in the control group. After given treatment, the average scores of the experimental class increased to 77.12, whereas it was 67.52 in the control class. Statistical analysis using SPSS and t-test confirmed a significant increase in vocabulary mastery in the experimental group, supporting the alternative hypothesis (Ha). Hence, collaborative learning with the WordUp application has significant effects on the vocabulary mastery of seventh-grade students at MTs Raudhatul Jannah Palangkaraya.